LEITURA, ENCONTRO COM OS(AS) OUTROS(AS): processos dialógicos no ato de ler. - GOMES, Kátia Cilene Amorim (2018)
The research entitled "READING, MEETING WITH OTHERS (AS): dialogic processes in the act of reading" is part of the Postgraduate Program in Management of Basic Education - PPGEEB, Professional Master's Degree, Research Line Teaching and Basic Education in the Federal University of Maranhão (UFMA) and its general objective is to develop a proposal for intervention on reading teaching in a dialogic perspective in the 2nd year of UEB Literacy Cycle "Justo Jansen", school of the Municipal Network of Teaching of São Luís - MA, aiming at the formation of readers (as). And, as specific: to identify the theoretical conceptions that underlie the work of the literacy teacher, with the teaching of reading and its implications for the formation of readers; to reflect on the limits and possibilities of work of reading teaching in the 1st Cycle of Elementary Education, in order to promote the formation of readers; to analyze the course of the proposal of intervention on the teaching of reading in a dialogical perspective, from the planning of didactic sequences aiming at the formation of readers; to produce a diary, supported by a book, describing the course of interventions on reading teaching in a dialogic perspective in the 2nd year of UEB Literacy Cycle "Justo Jansen" from the planning of didactic sequences. The objectives presented led us to the path of intervention research, based on the presuppositions of action research. The subject of the research was the teacher of the 2nd year of the 1st Cycle of Elementary Education, of the Basic Education Unit "Justo Jansen", of the academic year of 2017. The semistructured interview, the participant observation, as well as the analysis of the documents present in the space significantly contributed to the data generation process. Thus, Bakhtin and Volochinov (2014), in their theory, point out several aspects relevant to the understanding of the concept of language and its possible implications in the teaching of reading. We refer to contemporary authors who study reading, such as Foucambert (1994), Jolibert (1994), Smith (1989, 1999), Kleiman (2008, 2013), Smolka (2012), Mortatti (1995, 2000) ). From the studies and interventions carried out in the field of research we present the product "Book - Journal of Pedagogical Interventions in the 2nd year of the Literacy Cycle: dialogic experiences on the school floor" fruit of actions and reflections. The conclusions revealed that when the teaching of reading travels the way of work with the genres of discourse, therefore, in a dialogical perspective, the students advance in their learning, evolving from reading merely indexed in the decoding to a process of constructing meaning of the text read.